The URE2 gene product of Saccharomyces cerevisiae plays an important role in the cellular response to the nitrogen source and has homology to glutathione s-transferases. - Coschigano, P W (1991)
The URE2 gene of Saccharomyces cerevisiae has been cloned and sequenced. It encodes a predicted polypeptide of 354 amino acids with a molecular weight of 40,226. Deletion of the first 63 amino acids does not have any effect on the function of the protein. Studies with disruption alleles of the URE2 and GLN3 genes showed that both genes regulate GLN1 and GDH2, the structural genes for glutamine synthetase and NAD-linked glutamate dehydrogenase, respectively, at the transcriptional level, but expression of the regulatory genes does not appear to be regulated. Active URE2 gene product was required for the inactivation of glutamine synthetase upon addition of glutamine to cells growing with glutamate as the source of nitrogen. The predicted URE2 gene product has homology to glutathione S-transferases. The gene has been mapped to chromosome XIV, 5.9 map units from petX and 3.4 map units from kex2.